Les recettes de cuisine françaises peuvent-elles être protégées juridiquement? - Fringans, Thimothée (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2013)
The study aims at an analysis of legal protection of French culinary recipes. While the French-style gastronomic meal has been listed in the Cultural Immaterial World Heritage of UNESCO, the situation of the recipes in French law can be regarded as a  matter of great importance.  The presented study aims at examining the problem of whether the French legal rules for intellectual property protect recipes and culinary creations and are focused on the author’s copyright to the recipes. Patents, industrial designs or trademarks are not suited to providing culinary recipe protection. The secrets and know-how seem to be protected but only after the fact. As for the author’s rights, the recipe is merely treated as a work of literature.
French culinary recipes. Does the legal framework for intellectual property provide their protection?
Keywords: intellectual property law; copyrights; French culinary recipes